THE APPLICATION OF LESSON STUDY ASSISTED BY TWO STAY TWO STRAY COOPERATIVE MODEL TO IMPROVE ACTIVENESS AND LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Nilamsari Damayanti Fajrin; Sisca Wulandari (Widyagogik, 2020)
The purpose of this study is to determine the effectiveness of the application of lesson study in improving the quality of elementary school learning.  The improvement of learning quality can be seen from two indicators, which are increasing student activeness  and student learning outcomes.  The type of this research is a qualitative descriptive study.  The implementation of the study used 2 stages which is consisted of  the first stage, which was conducted by observing  the activeness and getting the learning outcomes in conventional learning;  and the second step, in which the lesson study step, consisting planning,  doing,  and seeing, assisted by the cooperative model TSTS was conducted. The results of the study increased student activiness and student learning outcomes during TSTS learning in lesson study.